Preeruptive Intracoronal Resorption: X-Ray and Tomographic Reports of Four Cases - Pérez Lip, Iván Eduardo (2023)
Preeruptive Intracoronal Resorption (PIR) manifests as a defect located in the dentin of a dental germ, adjacent to the amelodentinal junction in the crown. This defect, which varies in depth and anteroposterior location, can only be diagnosed through extraoral and intraoral x-rays, as well as dental tomography. The etiology of PIR remains undetermined, although histopathological studies suggest it could be a consequence of dental resorption. In this paper, panoramic x-rays and cone beam computed tomography (CBCT) scans of four patients with PIR are presented. The dental defects and enamel discontinuities adjacent to them are identified, highlighting the usefulness of CBCT in diagnosing and planning treatment for PIR cases.